Fundamentals of Graphics Communication - Bertoline Gary R. (Mc Graw Hill, 2005)
A thoroughly contemporary approach to teaching essential technical graphics skills has made Bertoline and Wiebe's Fundamentals of Graphics Communication the leading textbook in introductory engineering graphics programs. The fifth edition continues to integrate design concepts and the use of CAD into its outstanding coverage of the basic visualization and sketching techniques that enable students to create and communicate graphic ideas effectively.